Simulating the life course of psoriasis patients: the interplay between therapy intervention and marital status. (26th September 2017) - Linder, M.D.; Frigessi, A.; Piaserico, S.; Keilman, N.
Abstract: Background: Psoriasis, a chronic relapsing inflammatory disease affecting primarily the skin, shows multiple comorbidities including depression, cardiovascular diseases and other relevant conditions. Psoriasis patients experience social isolation, job loss, financial difficulties and partnership problems. Inversely, psychosocial impairments may negatively influence the disease course. Objective: To explore the feasibility of a model describing the interaction of psychosocial and clinical factors over the life course of patients. Methods: We considered only seven states for members of a hypothetical population: single and healthy, single and having a psoriasis flare, single and 'cured', coupled and healthy, coupled and having a psoriasis flare, coupled and 'cured', and dead. Transition probabilities between states were taken from the Norwegian Population Register for the healthy population and from epidemiological research articles. Clinical experience allowed adjustments on the assumed parameters. Results: Our macromodel, which simulates the effect of therapy intervention on patients' partnership status, yields a description of the transitions between the seven states. Treatment efficacy shows only a negligible effect on the chances of living with a partner. Conclusions: Mathematical modelling of interactions between social and health variables is in principle feasible. However, complex models, comprising more variables (for instance: employment status, depression level, obesity etc.), are needed for more realistic simulations for the interactions studied. As increasing the number of variables leads to an exponential increase of the model's state space, switching to micromodelling (representing each individual separately) may be necessary.